Genetics of Menopause and Primary Ovarian Insufficiency: Time for a Paradigm Shift? - Laven, Joop S. E. (Seminars in Reproductive Medicine, 2020)
This review summarizes the existing information concerning the genetic background of menopause and primary ovarian insufficiency (POI). There is overwhelming evidence that majority of genes are involved in double-strand break repair, mismatch repair, and base excision repair. The remaining loci were involved in cell energy metabolism and immune response. Gradual (or in case of rapid POI) accumulation of unrepaired DNA damage causes (premature) cell death and cellular senescence. This in turn leads to exhaustion of cell renewal capacity and cellular dysfunction in affected organs and eventually to aging of the entire soma. Similar erosion of the genome occurs within the germ cell line and the ovaries. Subsequently, the systemic “survival” response intentionally suppresses the sex-steroid hormonal output, which in turn may contribute to the onset of menopause. The latter occurs in particular when age-dependent DNA damage accumulation does not cease. Both effects are expected to synergize to promote (premature) ovarian silencing and install (early) menopause. Consequently, aging of the soma seems to be a primary driver for the loss of ovarian function in women. This challenges the current dogma which implies that loss of ovarian function initiates aging of the soma. It is time for a paradigm shift!
Keywords: menopause; primary ovarian insufficiency; genetics; fecundity; longevity